Optimization of grid-connected hybrid renewable energy system for the educational institutes in Pakistan - Mirza Abdullah Rehan (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
To foster resilient energy transition systems, the deployment of renewable energy sources is potentially helpful in the acceleration towards sustainable, reliable, and diversified solutions. In this feasibility study, aims to pursuit the best optimal solution for renewable energy resources, integrated into the local university's energy mix, to meet the electrical load demand of 8500 kWhr/day and a peak load of 815 kW. A model of a hybrid grid-connected renewable energy (PV/Biomass/Hydel/Diesel generator/Grid) system was implemented in HOMER software, to obtain the most efficient and cost-effective hybrid energy generation. The outcomes of the simulation seem more viable based on sensitivity analysis, as the cost of energy (COE) for an energy system with a hybrid combination is 0.13 $/kWh, meanwhile energy price with the grid system is 0.18 $/kWh. According to the HOMER analysis, a hybrid grid-connected PV/biomass/hydro system demonstrates both technological feasibility and economic viability, meanwhile it will also save 1575 tons of CO2 per year. Therefore, this proposed hybrid energy system, a step towards sustainable development, can be applied at institutional levels, especially in developing countries.